A monocyte‐TNF‐endothelial activation axis in sickle transgenic mice: Therapeutic benefit from TNF blockade. Issue 11 (29th July 2017) - Solovey, Anna; Somani, Arif; Belcher, John D.; Milbauer, Liming; Vincent, Lucile; Pawlinski, Rafal; Nath, Karl A.; Kelm, Robert J.; Mackman, Nigel; O'Sullivan, M. Gerard; Gupta, Kalpna; Vercellotti, Gregory M.; et al.
Abstract: Elaboration of tumor necrosis factor (TNF) is a very early event in development of ischemia/reperfusion injury pathophysiology. Therefore, TNF may be a prominent mediator of endothelial cell and vascular wall dysfunction in sickle cell anemia, a hypothesis we addressed using NY1DD, S+S Antilles, and SS‐BERK sickle transgenic mice. Transfusion experiments revealed participation of abnormally activated blood monocytes exerting an endothelial activating effect, dependent upon Egr‐1 in both vessel wall and blood cells, and upon NFκB(p50) in a blood cell only. Involvement of TNF was identified by beneficial impact from TNF blockers, etanercept and infliximab, with less benefit from an IL‐1 blocker, anakinra. In therapeutic studies, etanercept ameliorated multiple disturbances of the murine sickle condition: monocyte activation, blood biomarkers of inflammation, low platelet count and Hb, vascular stasis triggered by hypoxia/reoxygenation (but not if triggered by hemin infusion), tissue production of neuro‐inflammatory mediators, endothelial activation (monitored by tissue factor and VCAM‐1 expression), histopathologic liver injury, and three surrogate markers of pulmonary hypertension (perivascular inflammatory aggregates, arteriolar muscularization, and right ventricular mean systolic pressure). In aggregate, these studies identify a prominent—and possibly dominant—role for an abnormal monocyte‐TNF‐endothelial activation axis in the sickle context. Its presence, plus the many benefits of etanercept observed here, argue that pilot testing of TNF blockade should be considered for human sickle cell anemia, a challenging but achievable translational research goal.